Impact of Workforce Diversity on Employee Performance With Reference to IT Companies of Udaipur - Shekhawat, Shakti Singh; Sarangdevot, SS (International Journal of Computer Sciences and Engineering, 2025)
IT industry is rapidly growing Industry in India. Workforce diversity is the emerging issue in today’s corporate world as it’s not only a challenge for the organizations but also a chance, which if not properly managed can affect the performance of employees and therefore the organization. People are different in not only in gender, age, education, ethnic diversity but also in their perspectives and prejudices. The impact of diversity in the workplace is surprisingly greater than one would think. Studies show that putting together a team composed of people with the same ethnic background and personality may cause conflicts and decrease productivity. As opposed to a team that is composed of people with different ethnic backgrounds and personalities which allows for a higher rate of productivity and a lower rate of conflict. The aim of the present study is to identified the impact of various diversity on employee performance of IT companies of Udaipur. There are numerous diversity factors that can affect employee performance, but this study included only the most critical variables among all of them, such as diversity in age, gender, ethnicity, educational background, religious, workforce, and employee attitude towards job, which were independent variables, and employee performance in an organisation, which was a dependent variable. The data for this study was gathered by sending questionnaires to 300 employees of multiple IT companies in the Udaipur District of Rajasthan (India). The empirical link between age, gender, ethnicity, educational background, religion, workforce, and job attitude was calculated using the Software Package for Social Science (SPSS). Statistical methods such as the percent and Chi-Square Test, the 't' test, and correlation were utilised to examine the SPSS data. The study's findings revealed that all work force diversity characteristics are favourably connected with employee performances.